Pengaruh Pijat Bayi terhadap Kualitas Tidur Bayi Usia 0 - 11 Bulan - Faizaturrahmi, Eka; Aprianti, Nurannisa Fitria (STIKes Hamzar, 2024)
Sleep and rest are one of the factors that influence a child's growth and development, because when a baby is asleep, three times more growth hormone is secreted than when the baby is awake. Because sound sleep is very important for growth, especially for babies. During sleep, baby's brain growth reaches its peak. The aim of this research is to determine the effect of baby massage on sleep quality in babies aged 0-11 months at Nur Azhari Mom & Baby SPA. This research design is pre-experimental research using a One Group Pretest-Posttest Design. The sample consisted of 11 people obtained using Purposive Sampling. Data collection uses primary data and secondary data. Data processing uses univariate and bivariate analysis. The results of this study were that the average sleep quality of babies aged 0-11 months before baby massage stimulation and after baby massage was 5.5 with a significant number (0.004) much lower than the significant standard of 0.05. The conclusion of the research results shows that there is an influence of massage on the sleep quality of babies aged 0-11 months at Nur Azhari Mom & Baby SPA.